The Impact of a Baseline Exercise Test on Confidence to Perform Subsequent Incremental Shuttle Walk Tests, Walk at Home, and Manage Breathlessness. Issue 2 (9th March 2022) - Stenson, Amy; Chaplin, Emma J.; Houchen-Wolloff, Linzy; Singh, Sally J.
Abstract : We investigated whether performing an incremental shuttle walk test during a pulmonary rehabilitation assessment might alter perceived ability to exercise. Confidence increased, but this was not related to changes in performance. Respiratory research trials need to consider that conducting baseline exercise tests may affect future exercise behaviors. Abstract : Purpose: Incremental shuttle walk tests (ISWTs) are routinely conducted as outcome measures in pulmonary rehabilitation (PR) assessments and in clinical trials; however, there is a paucity of data describing the impact of simply conducting an exercise test and the change produced in the perceived ability of the individual to perform exercise subsequently, which may in turn influence therapy and study outcomes. Methods: We conducted a prospective observational cohort study at Glenfield Hospital, Leicester, UK (University Hospitals of Leicester NHS Trust). At initial PR assessment, we asked patients pre- and post-practice ISWT to report confidence in three areas (walking at home [Q1], managing breathlessness [Q2], and performing an ISWT [Q3]) based on a visual analog scale (0-10). Results: A total of 100 patients with chronic respiratory disease (age 68.0 ± 10.3 yr, male 49%, chronic obstructive pulmonary disease 63%, Medical Research Council 2-5) completed visual analog scale confidence questions pre- and post-practice ISWT. Confidence in all questions improved after a practice ISWT (all P < .01 Wilcoxon signed rank). A statistically significant improvement in ISWT distance was noted (practice ISWT 207.3 ± 132.7 m to second ISWT 227.4 ± 142.0 m, mean difference = 20.1 m). No association was found between changes in confidence and changes between walk 1 and walk 2 ( r 2 = [Q1] −0.04, [Q2] −0.09, [Q3] 0.04, P >.05). Conclusions: Confidence increased in all areas post-practice ISWT, but this was not related to changes in performance. However, this change may be an important consideration when designing research trials as exercise behaviors (eg, walking at home) may be affected by conducting baseline exercise tests.